Effects of annealing on laser clad Ti2SC/CrS self-lubricating anti-wear composite coatings on Ti6Al4V alloy: Microstructure and tribology. (September 2016) - Lu, Xiao-Long; Liu, Xiu-Bo; Yu, Peng-Cheng; Fu, Ge-Yan; Zhu, Gang-Xian; Wang, Yong-Guang; Chen, Yao
Abstract: Laser clad NiCr/Cr3 C2 coating and Ti2 SC/CrS self-lubricating anti-wear composite coating using NiCr/Cr3 C2 –WS2 powders were fabricated on Ti6Al4V substrates. Effects of annealing on microstructure, microhardness and tribological properties of the Ti2 SC/CrS composite coatings had been investigated systematically. Results indicated that the annealing process did not have significant effects on the phase constituents and microhardness. Compared with NiCr/Cr3 C2 coating, the Ti2 SC/CrS coating shows good anti-wear and friction-reducing properties owing to the existence of in situ synthesized self-lubricating phases Ti2 SC and CrS. Furthermore, after the appropriate annealing process (at 600 °C for 1 h), the anti-wear property of the Ti2 SC/CrS coating could be significantly enhanced and is beneficial to the running-in surface of the counter-body. Highlights: Self-lubricating anti-wear composite coatings were fabricated on Ti6Al4V by laser cladding. Effects of annealing on coatings have been investigated systemically. Coating presents excellent anti-wear and friction reducing properties after annealing.